War contemporary perspectives on armed conflicts around the world - Lippard, Cameron D.; Osinsky, Pavel; Strauss, Lon (Routledge, Taylor & Francis Group, 2018)
War: Interdisciplinary Perspectives on Armed Conflicts around the World presents a broad variety of interdisciplinary social scientific perspectives on the causes, processes, cultural representations, and social consequences of the armed conflicts between and within nations and other politically organized communities. Composed of framing essays and original readings, this book provides theoretical views of armed conflict and its impact on people and institutions around the world."--Provided by publisher